Superwomen Fitness Management System - Badrul Kamal, Shaza Athirah; Mohd. Yasin, Suhaila (Applied Information Technology And Computer Science, 2025)
The Superwomen Fitness Management System (SFMS) aims to address the challenges faced by fitness centers due to outdated management methods. This web-based platform will streamline operations, offering features such as user registration, fitness assessments, personalized training programs, and progress monitoring. Designed with object-oriented principles, SFMS ensures scalability and maintainability while catering to admins, fitness trainers, and members. By reducing administrative burdens and improving data accuracy, SFMS will enhance efficiency and customer satisfaction. Rigorous testing, including unit, integration, and user acceptance testing, will validate the system's functionality, reliability, and performance. SFMS will revolutionize fitness center management, providing a digital solution that meets the evolving demands of the industry, improves operational efficiency, and enhances user experiences.